2019
DOI: 10.1093/jxb/erz012
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and modeling evidence of carbon limitation of leaf appearance rate for spring and winter wheat

Abstract: Carbon availability can account for environmental effects on leaf appearance rate (LAR) and a new ecophysiological model is developed that gives good predictions for LAR in contrasting field environments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 79 publications
(117 reference statements)
1
21
0
Order By: Relevance
“…The phyllochron describing leaf appearance rate responds nonlinearly to multienvironmental factors. When it is modeled using only temperature, residual environmental effects are often observed (Cao and Moss, 1989;Baumont et al, 2019). This can be partly removed using the photothermal time corresponding to temperatures accumulated during the light time period only (Masle et al, 1989).…”
Section: Assimilation Of Gf Observations Provides Accurate Estimates mentioning
confidence: 99%
“…The phyllochron describing leaf appearance rate responds nonlinearly to multienvironmental factors. When it is modeled using only temperature, residual environmental effects are often observed (Cao and Moss, 1989;Baumont et al, 2019). This can be partly removed using the photothermal time corresponding to temperatures accumulated during the light time period only (Masle et al, 1989).…”
Section: Assimilation Of Gf Observations Provides Accurate Estimates mentioning
confidence: 99%
“…For example, Legris et al (2016) have shown that phytochrome B is not only related to photoperiod but also to temperature sensitivity. Baumont et al (2019) relate leaf appearance rate with carbohydrate availability and claim that the photoperiod effect of leaf appearance rate could be a surrogate for carbohydrate availability. And one could think that as our knowledge of the gene network controlling phenology improves, models will improve as well; but will models accelerate the uncovering of these networks?…”
Section: Phenologymentioning
confidence: 99%
“…Defining the canopy greenness throughout the growth cycle is critical to compute transpiring (green area) and non-transpiring fractions of the canopy. Leaf development is largely a function of temperature and carbohydrates availability (Baumont et al, 2019), but leaf expansion is also controlled by water and nutrient stress.…”
Section: Canopy Developmentmentioning
confidence: 99%
“…In rice, Islam and Morison (1992) introduced the photothermal quotient (PQ) -as the ratio between cumulated radiation and cumulated thermal time (MJ.m -2 .°C -1 ) -during the 30 days-day period before harvest in order to predict yield. Recently, Baumont et al (2019) indicated in wheat the joint role of temperature and carbon availability on plant development rate and concluded that the use of photothermal quotient (PQ) is relevant to better model cycle durations in different light and temperature environments. In order to compare phyllochron between environments, it is suggested here that thermal time is appropriate when environments differ mainly by their temperature conditions, while PQ is when facing contrasted environments, differing by incident radiation, temperature and VPD, as it was the case in our study.…”
Section: Phenotyping For Tolerance To Mild Water Deficit At Reproductmentioning
confidence: 99%